Approaches to international investment protection: Divergent approaches between the TPPA and developing countries' model investment treaties - Kinda Mohamadieh; Daniel Uribe (South Centre, 2016)
While the international investment treaty regime is at a conjuncture, States face the challenge of designing reforms that would result in systemic solutions, and not merely cosmetic changes, to the challenges emerging out of the existing regime and the ISDS mechanism it embodies. While many countries are reviewing and introducing changes to their treaty practice, which is often proclaimed as 'reforms', countries are taking significantly different steps and approaches in this area. This paper highlights that the vision for the future of the investment protection rules presented by India and Brazil under their new model treaties is substantively and significantly different from those presented under the TPP investment chapter. The latter has been assessed as a model that "entrenches rather than reforms" the existing flawed system.
Keywords: 300; Auslandsinvestition; Protektionismus; Handelsabkommen; Vergleich; USA; Indien; Brasilien